AMD Genetics in India: The Missing Links - Anand, Akshay; Sharma, Kaushal; Sharma, Suresh K.; Singh, Ramandeep; Sharma, Neel K.; Prasad, Keshava (Frontiers in Aging Neuroscience, 2016)
Age related macular degeneration is a disease condition which occurs in aged peoples. There are various changes occurs at the cellular, molecular and physiological levels with age (Kaushal et al, 2013; Samiec et al 1988). Drusen deposition between RPE and Bruch’s membrane is one of the key features in AMD patients (Mullins RF et al, 2000; Hagemana et al, 2001) as Aβ/tau aggregates in AD patients. The primary goal of this review is to discuss whether the various candidate genes and associated biomarkers, that are supposed to play an independent role in progression of AMD, exert deleterious effect on phenotype, alone or in combination, in Indian AMD patients from the same ethnic group. A statistical model for probable interaction between genes could also be derived from such analysis. We can use multiple modalities to identify and enrol AMD patients based on established clinical criteria and examine the risk factors to determine if these genes are associated with risk factors, biomarkers or disease by Mendelian randomization. Similarly, there are large numbers of single nucleotide polymorphisms (SNPs) identified in human population. Even non-synonymous SNPs (nsSNPs) are believed to induce deleterious effects on the functionality of various proteins. The study of such snSNPs could provide a better genetic insight for diverse phenotypes of AMD patients, predicting significant risk factors for the disease. Therefore, the prediction of biological effect of nsSNPs in the candidate genes is highly solicited. Therefore, genotyping and levels of protein expression of various genes would provide bigger canvas in genetic complexity of AMD pathology which should be evaluated by valid statistical and bioinformatics’ tools. Longitudinal follow up of Indian AMD patients to evaluate the temporal effect of SNPs and biomarkers on progression of disease could also provide unique strategy in the field.